An Assessment of Potable Water Quality at Kolej Kediaman Kampus Pagoh, Universiti Tun Hussein Onn Malaysia - SELIYAN, KYIIRTHANA; Muslim, Rahmat (Progress in Engineering Application and Technology, 2023)
Water quality is an essential requirement of human life and activities associated with industry, agriculture, and others, and it considers one of the most delicate parts of the environment. This study was carried out to determine the University Tun Hussein Onn Malaysia Pagoh Campus Student Residential College 1 (A1), 2 (A14) and 3 (A17) water quality to ensure the level of water hardness parameter met the usable standard at the supply point of the pipe. This study was carried out based on the responses from students that the water quality of the hostel is affecting them which can lead to some health issues such as hair loss, and skin becoming dry and itchy when consuming the hostel’s water. There were five parameters namely pH, Temperature, Hardness, Manganese, and Chemical Oxygen Demand (COD) were employed in this study to determine the water quality. To measure these parameters the researcher conducted laboratory testing to gather exact data that can be very easy to analyse and comply with Malaysian Drinking Water Quality Standard (MDWQS). This research will carry out by using the most advanced DR 6000 UV-VIS lab spectrophotometer HACH method to quantitative analysis of water quality parameters. For temperature, pH, hardness, manganese, and COD, the range for each parameter between 27.26 ℃ to 32.38 ℃, 7.1 to 7.6, 20.3mg/l to 39.7mg/l, 0.2mg/l to 1.0mg/l and 10mg/l to 25mg/l. The values of each parameter were found to be within the safe limits set by (MDWQS) except for the manganese level. This study is to provide benefits to university students which included those from different states, so they can use the Hostel’s water without any inconvenience and without affecting their health during their study period.